BOAS - Generating a Safety Culture - Rodríguez Portocarrero, Pavel (2017)
This article is based on the foundations of the psychological trend called «behaviorism» and the preventive tool called safety based on behavior (SBB). Model behavioral observation applied to safety (BOAS) is a complement for the Management of Occupational Safety and Health, which aims to increase safe behavior of employees in an organization, looking at the short term generate workers attitude change (shown in their behavior) and long term by generating a safety culture that internalizes the worker and adopt as his own, bringing learning taught by the organization to all aspects of their daily lives. During the development of this article the implementation process, maturity and improvement of the Model BOAS is displayed. As the results show the gradual increase in safe behavior of workers in the organization.